How Comparable are Microbial Electrochemical Systems around the Globe? An Electrochemical and Microbiological Cross‐Laboratory Study. Issue 11 (5th May 2021) - Santoro, Carlo; Babanova, Sofia; Cristiani, Pierangela; Artyushkova, Kateryna; Atanassov, Plamen; Bergel, Alain; Bretschger, Orianna; Brown, Robert K.; Carpenter, Kayla; Colombo, Alessandra; Cortese, Rachel; Erable, Benjamin; et al.
Abstract: A cross‐laboratory study on microbial fuel cells (MFC) which involved different institutions around the world is presented. The study aims to assess the development of autochthone microbial pools enriched from domestic wastewater, cultivated in identical single‐chamber MFCs, operated in the same way, thereby approaching the idea of developing common standards for MFCs. The MFCs are inoculated with domestic wastewater in different geographic locations. The acclimation stage and, consequently, the startup time are longer or shorter depending on the inoculum, but all MFCs reach similar maximum power outputs (55±22 μW cm −2 ) and COD removal efficiencies (87±9 %), despite the diversity of the bacterial communities. It is inferred that the MFC performance starts when the syntrophic interaction of fermentative and electrogenic bacteria stabilizes under anaerobic conditions at the anode. The generated power is mostly limited by electrolytic conductivity, electrode overpotentials, and an unbalanced external resistance. The enriched microbial consortia, although composed of different bacterial groups, share similar functions both on the anode and the cathode of the different MFCs, resulting in similar electrochemical output. Abstract : The famous five : A cross‐laboratory study involving five institutions is presented. Each team runs a triplicate identical single chamber microbial fuel cell for 6 weeks varying only the inoculum. Electrochemical and operational parameters are collected. Microbiological analysis is carried out on the influent and effluent and on the electrodes. All the data collected are correlated by using robust statistics.